2018
DOI: 10.1093/jisesa/iey097
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod Facilitation by Wood-Boring Beetles: Spatio-temporal Distribution Mediated by a Twig-girdler Ecosystem Engineer

Abstract: The twig-girdler beetle Oncideres albomarginata chamela (Chemsak and Giesbert) (Cerambycidae: Lamiinae) detaches branches of Spondias purpurea L. (Sapindales: Anacardiaceae) that fall on the forest floor or remain suspended on vegetation. Many wood-boring beetles also oviposit in these branches and larval development creates cavities that are abandoned when the adults emerge. The objective of this study was to evaluate the role of wood-boring beetles as facilitators by creating new habitats for arthropods, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…A dichotomic seasonal (transition between rainy and dry seasons) pattern differentiated by precipitation, has been observed in tropical regions for various groups of insects (Kishimoto-Yamada & Itioka, 2015; Novais et al, 2016) and for different families of beetles in the TDF (Toledo-Hernández et al, 2015; Macedo-Reis et al, 2016; Corona-López et al, 2017; Novais et al, 2018b). For the Cerambycidae communities, this pattern has been recognized in the TDF of different regions of Mexico (Noguera et al, 2002; Noguera et al, 2007; Noguera et al, 2009; Noguera et al, 2012; Toledo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dichotomic seasonal (transition between rainy and dry seasons) pattern differentiated by precipitation, has been observed in tropical regions for various groups of insects (Kishimoto-Yamada & Itioka, 2015; Novais et al, 2016) and for different families of beetles in the TDF (Toledo-Hernández et al, 2015; Macedo-Reis et al, 2016; Corona-López et al, 2017; Novais et al, 2018b). For the Cerambycidae communities, this pattern has been recognized in the TDF of different regions of Mexico (Noguera et al, 2002; Noguera et al, 2007; Noguera et al, 2009; Noguera et al, 2012; Toledo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Cerambycidae beetles are of great ecological importance in forest ecosystems. Their larvae are saproxilophagous (saprophagous/xylophagous), and thus they are key species in the process of wood decomposition (Noguera & Chemsak, 1996; Hovore, 2006; Calderón-Cortés, Quesada & Escalera-Vázquez, 2011; Novais et al, 2018b). The imagos (adult stage) of different species feed on sap, leaves, flowers, fruits, bark and fungi (Monné & Bezark, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At large scales, dead wood in the form of dying and dead trees, standing or fallen branches at different stages of decay are important resources (e.g., food, shelter, and breeding sites) for the conservation of a large number of species, such as saproxylic insects, lichens, bryophytes, birds, and mammals; Radu 2006). At a fine scale, we highlight the importance of dead plant tissues in the form dead branches attached on living trees and fallen branches hanged on vegetation as potential refugia that maintain arthropod diversity, which can be mediated by insects such as wood-boring beetles (Novais et al 2018) or through abandoned dead domatia as demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in the same tropical dry forest demonstrated the role of wood-boring beetles as important habitat facilitators for arthropods, which utilize the abandoned cavities made by beetle larvae during their development in the wood (Novais et al 2018). Comparing the arthropod community that reused both abandoned cavities (branches vs domatia), Novais et al (2018) found that spiders (115 individuals), centipedes (37), and crickets (30) were the most abundant nonsocial arthropods in a set of 240 Spondias purpurea L. (Anacardiaceae) branch samples. In the present study, we found only four spiders, seven centipedes, and no crickets within a total of 380 domatia samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation